2022
DOI: 10.1039/d2mh00566b
|View full text |Cite
|
Sign up to set email alerts
|

Reversible color modulation of luminescent conjugated polymers based on a chemical redox mechanism and applications in rewritable paper and multiple information encryption

Abstract: Reversible color modulation plays a key role in the field of information recording and encryption, but for the common colorful conjugated polymer materials, currently it still lacks a convenient method...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…3.1.2 Modified molecular structure. Over the past few years, great achievements have been made in modulating the color of organic EC materials by modifying the molecular structure, [76][77][78] which is also considered to be one of the most important strategies to achieve color tuning of EC materials. Using this strategy, a lot of green and yellow EC materials for adaptive color camouflage have been designed and synthesized, such as small organic molecules, [79][80][81][82] metal-organic complexes, 83,84 and conjugated polymers.…”
Section: Ec Materials For Color Camouflagementioning
confidence: 99%
“…3.1.2 Modified molecular structure. Over the past few years, great achievements have been made in modulating the color of organic EC materials by modifying the molecular structure, [76][77][78] which is also considered to be one of the most important strategies to achieve color tuning of EC materials. Using this strategy, a lot of green and yellow EC materials for adaptive color camouflage have been designed and synthesized, such as small organic molecules, [79][80][81][82] metal-organic complexes, 83,84 and conjugated polymers.…”
Section: Ec Materials For Color Camouflagementioning
confidence: 99%
“…Li et al synthesized 3,4-propylenedioxythiophene (ProDOT)-based conjugated polymers that underwent reversible chemical redox reactions in the presence of Fe 3+ and Fe 2+ using the redox concept. The polymer printed paper demonstrated outstanding stability in ambient air at a relative humidity (RH) of 5%–15% and recyclability (writing and erasing) up to 15–20 cycles . From the above discussion, it can be concluded that depending on the nature of the stimuli-responsive moiety, the conditions of writing and erasing can be assessed.…”
Section: Introductionmentioning
confidence: 96%
“…The polymer printed paper demonstrated outstanding stability in ambient air at a relative humidity (RH) of 5%−15% and recyclability (writing and erasing) up to 15−20 cycles. 28 From the above discussion, it can be concluded that depending on the nature of the stimuli-responsive moiety, the conditions of writing and erasing can be assessed. Additionally, it is crucial to form a thin film on a flexible and foldable paper.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence‐based sensors exhibit promising potential in biology, pharmacology, and environmental fields due to their low‐cost, excellent selectivity and sensitivity, quick detection, and low detection limits. [ 19–31 ] Unfortunately, there are currently no fluorescent probes reported to detect propanol solvents, especially for the distinction of propanol isomers. Considering the difference of electron‐withdrawing abilities between isopropanol and n ‐propanol isomers, one of the promising solutions is to design a fluorescent probe that is sensitive to them due to the change of excited state characteristic.…”
Section: Introductionmentioning
confidence: 99%